2017
DOI: 10.5751/es-09662-220418
|View full text |Cite
|
Sign up to set email alerts
|

A coupled terrestrial and aquatic biogeophysical model of the Upper Merrimack River watershed, New Hampshire, to inform ecosystem services evaluation and management under climate and land-cover change

Abstract: ABSTRACT. Accurate quantification of ecosystem services (ES) at regional scales is increasingly important for making informed decisions in the face of environmental change. We linked terrestrial and aquatic ecosystem process models to simulate the spatial and temporal distribution of hydrological and water quality characteristics related to ecosystem services. The linked model integrates two existing models (a forest ecosystem model and a river network model) to establish consistent responses to changing drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
0
24
0
1
Order By: Relevance
“…Climate change, unlike LULC change, has quite large impacts on hydrologic simulations [31] and ES. Fan et al [29] found the climate scenario results in much more water yield than LULC scenario as future climate scenario created consistently increased water yield while LULC increased and then decreased water yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change, unlike LULC change, has quite large impacts on hydrologic simulations [31] and ES. Fan et al [29] found the climate scenario results in much more water yield than LULC scenario as future climate scenario created consistently increased water yield while LULC increased and then decreased water yield.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive, temporally explicit framework that couples hydrologic and ES modeling would effectively accelerate the ES modeling processes. Studies have been conducted with a few different types of hydrologic and ES models for hydrologic ES [28][29][30][31][32]. Cline et al [24] combined a hydrologic model with an ES model to evaluate the spatial and temporal patterns of fish density in the resident fish populations.…”
Section: Introductionmentioning
confidence: 99%
“…With the ability of this framework to simulate monthly and seasonal ES output, these extreme events could be captured and related remedies could be designed. Unlike previous ES studies [16,21], the flooding regulation ES simulated in this study can not only predict the flooding risk per year but also pinpoint the months and seasons when regulation for ES should be applied.…”
Section: Introductionmentioning
confidence: 98%
“…The first hydrologic ES variable is water provision ES. Limited studies have been conducted with a focus on water-related ES [14][15][16][17][18], with only a few of them on a seasonal or monthly basis [19,20]. Compared to Notter et al [19], who used monthly hydrologic results to calculate the ES indices, this study not only uses daily hydrologic data but also produces monthly and seasonal ES indices which can provide more detailed information for decision makers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the value assessment of land use and value coefficient, changes in land use will inevitably lead to changes in the value of ecological service, but it cannot reflect the intrinsic driving factors of the changes in the value of ecological service. Climate was very important to the spatial distribution of ecological service value [11][12][13], especially water-related ecosystem services [14][15][16][17]. In some studies, the selection of influencing factors was relatively casual, and the multicollinearity problem between the influencing factors was not considered.…”
Section: Introductionmentioning
confidence: 99%